(3GdCZGfj hGdCdMGfs
(3ChdgG (B:s
(3PhGdeYGdj hGdceGd aGNQ HMOjf SGA deG Mjf JSei aj NUhQ GdRjf OhQ HOjY GdeMjG CnOrQ dj GdcDhS hfhQ GdeMjG jahb GdTehS s
(3BNQgG (B:s
(3TeS GdLeGd NHJ HHOQcf hVMG GdgdGd bO MLHJg Yjf YbO GddBdj Ydi GdKfGjG aGb GdLeGf s
(3jMJhj Ydi COhGQ eJVefI HYV GdCdaGX GdYGejIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B47 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ MSjf Ydj eMahX HHZOGO (B(149) s
Keywords: (3GdCOHs